The role of targeting glucose metabolism in chondrocytes in the pathogenesis and therapeutic mechanisms of osteoarthritis: a narrative review - Pi, Peng; Zeng, Liqing; Zeng, Zhipeng; Zong, Keqiang; Han, Bing; Bai, Xizhe; Wang, Yan (Frontiers in Endocrinology, 2024)
Osteoarthritis (OA) is a common degenerative joint disease that can affect almost any joint, mainly resulting in joint dysfunction and pain. Worldwide, OA affects more than 240 million people and is one of the leading causes of activity limitation in adults. However, the pathogenesis of OA remains elusive, resulting in the lack of well-established clinical treatment strategies. Recently, energy metabolism alterations have provided new insights into the pathogenesis of OA. Accumulating evidence indicates that glucose metabolism plays a key role in maintaining cartilage homeostasis.Disorders of glucose metabolism can lead to chondrocyte hypertrophy and extracellular matrix degradation, and promote the occurrence and development of OA. This article systematically summarizes the regulatory effects of different enzymes and factors related to glucose metabolism in OA, as well as the mechanism and potential of various substances in the treatment of OA by affecting glucose metabolism. This provides a theoretical basis for a better understanding of the mechanism of OA progression and the development of optimal prevention and treatment strategies.